ALTRUISTIK PENGORBANAN YESUS SEBAGAI IMPLEMENTASI EKO-PASTORAL: KEPEDULIAN TERHADAP LINGKUNGAN - Taruh, Sannya Sari (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2025)
Jesus' sacrifice is an example of His saving work in relieving people from the bondage of sin and directing people to the expression of their faith in Him. Jesus' sacrifice was not only seen as redemption but also as his altruistic act to the man he created because of his great love he made a sincere sacrifice to man. The Church today needs to interpret and apply how altruism (caring for voluntarily helping, and emphasizing justice) in the Alttuistic and the sacrifice of Jesus is manifested through His love, empathy and solidarity with people and the environment. So that humans can free themselves and others and free the environment from anthropocentric human attitudes through eco-pastoral to get out of the problem of social crisis (marginalization). In this study, the researcher used the literature method, because it is therefore possible to deduce various kinds of relevant literature.